OBSERVATIONS ON THE FEEDING HABITS OF YOUNG CARP FRY - Alikunhi, K.H. (Indian Journal of Fisheries, 2015)
In an earlier contribution, the author (Alikunhi, 1952) demonstrated thai zooplankton constituted the ' main food' of tender carp fry and that phytoplankton was consumed only a s ' emergency food'. Differenceis in the digestibility of zooplankton and phytoplankton organisms were also indicated and it was found that maximum survival and growth of fry were obtained when they were fed on zooplankton.